An overview of regulation for nutraceuticals and concept of personalized nutraceuticals. (June 2023) - Tomar, Saurav; Musyuni, Pankaj; Aggarwal, Geeta
Nutraceuticals are essentially nutritional components that have a vital role in developing and maintaining the body's regular functions, which keeps people healthy. The nutraceutical sector is also primarily driven by the existing global population and trends. Examples of foods considered as nutraceuticals include prebiotics, fibre, polyunsaturated fatty acids, probiotics, antioxidants, and other natural or herbal foods. Some of the most serious health problems of the 20th century, like COVID-19 and diabetes mellitus, are managed with the help of the preceding nutraceuticals. As we move into a time of health and medicine, the food industry as a whole has become more focused on research.